The Impact of Household Shocks on Domestic Violence: Evidence from Tanzania - Olukorede Abiona; Martin Foureaux Koppensteiner (Institute of Labor Economics (IZA), 2018)
In this paper, we study the effect of household shocks on the incidence of domestic violence using household survey microdata from Tanzania. We use idiosyncratic variation in rainfall to proxy for shocks on household income of rural households. We find that droughts lead to a considerable increase of domestic violence in the households. A one standard deviation negative rainfall shock from the long-term mean increases the incidence by about 13.1 per cent compared to the baseline. We make use of the rich information from the household survey to investigate the underlying pathways.
Keywords: D13; I10; J12; J16; 330; domestic violence; household shocks; rainfall; Tanzania